Abiotic environmental variation drives virulence evolution in a fish host–parasite geographic mosaic. (10th July 2017) - Mahmud, Muayad A.; Bradley, Janette E.; MacColl, Andrew D. C.
Abstract: Parasite virulence varies greatly. Theory predicts that this arises from parasites optimising a trade‐off between the mortality they inflict on current hosts, and their transmission to future hosts. The effect of the environment on this co‐evolution is rarely considered. Geographic mosaics are fertile systems for studying co‐evolution, but again, the diversity of outcomes is often assumed to result from co‐evolutionary dynamism, rather than being moulded by the environment. Here, we quantify variation in virulence among lakes in a geographic mosaic of co‐evolution between a trematode ectoparasite ( Gyrodactylus arcuatus ) and its three‐spined stickleback ( Gasterosteus aculeatus ) host. Virulence varies greatly in this system, and parasites are generally locally adapted to their hosts. Parasites are also locally adapted to the water in their own lake, and virulence is strongly related to lake pH, the dominant axis of abiotic environmental variation in this system. These results suggest that the evolution of virulence can be substantially affected by the abiotic environment, which has important implications for understanding co‐evolution. There are also implications for the evolutionary management of disease, e.g. ectoparasites in aquaculture, the impacts of which might be expected to reduce given ongoing acidification of aquatic ecosystems. A plain language summary is available for this article. Abstract : Plain Language Summary